The Semiotic Analysis of Da’wah Symbols in Qasidah Shalawat within the Badui Kubro Siswo Art Performance - Ainun Amaliya Paramita; Ahmad Amiruddin Priyatmaja; Alqodri Alqodri; Puji Pangestuti (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
his study analyzes the shiar da’wah of Qasidah Shalawat within the traditional art of Badui Kubro Siswo in Tambakan Hamlet, Sinduharjo, Ngaglik, Sleman, Yogyakarta, and explores its relevance to Islamic educational values. Employing a qualitative descriptive method with a historical approach, data were obtained through observation, interviews, and documentation. The findings reveal that Badui Kubro Siswo, which has been preserved since the 1960s, serves not merely as a form of entertainment but as a medium of cultural da’wah that harmonizes Islamic values with Javanese traditions. The qasidah verses, costumes, and choreographed movements embody messages of faith, Islamic law, morality, and nationalism, including principles of amar ma’ruf nahi munkar, respect for guests, and love for the homeland. Historically, this art emerged as a community response to limited understanding of religious practices, evolving into a vehicle for internalizing Islamic teachings in daily life. The study concludes that Badui Kubro Siswo art plays a strategic role in promoting Islamic education, fostering moral and religious character, and preserving the cultural identity of Islam amid globalization. Its integrative nature highlights the potential of local arts as instruments of values-based education and spiritual communication within Muslim societies.